The effect of subthalamic stimulation on viscoelastic stiffness of skeletal muscles in patients with Parkinson's disease. (May 2017) - Rätsep, Tõnu; Asser, Toomas
Abstract: Background: Myotonometric evaluation of viscoelastic stiffness of skeletal muscles has been proposed to document the effect of surgical or pharmacological treatment on rigidity in patients with Parkinson's disease. The aim of the study was to analyze the changes of viscoelastic stiffness induced by deep brain stimulation. Methods: Fifteen patients in an advanced stage of Parkinson's disease participated in the study. The study took place in the off-medication conditions after one night of drug withdrawal. The Unified Parkinson's Disease Rating Scale was used for clinical assessment of the disease. Myotonometry was used to measure viscoelastic stiffness in the resting muscles before and directly after passive wrist movements, commonly used for clinical evaluation of rigidity. The measurements were repeated during the stimulation-on and stimulation-off periods and compared with fifteen healthy control persons. Findings: The clinical scores for wrist rigidity improved from 3.0 (1–4) to 0.93 (0–2) ( P < 0.05) due to brain stimulation. The mean values of viscoelastic stiffness were similar before and after passive wrist movements, but the differences between the patients with high vs. low rigidity values (354.9 vs 310.2 N/m; P < 0.05) and in stimulation-off vs. stimulation-on conditions (342.7 vs 310.5 N/m; P < 0.05) were significant only if the measurements had been performed after passive wrist movements. Interpretation: Effective deep brain stimulation and increased rigidity can significantly change viscoelastic stiffness in the resting muscles in patients with Parkinson's disease, especially if evaluated after passive wrist movements. This paper supports the use of myotonometry for objective quantification of parkinsonian rigidity at rest. Highlights: Viscoelastic stiffness is elevated in patients with higher parkinsonian rigidity. Deep brain stimulation decreases the values of viscoelastic stiffness. Myotonometry can be used for objective quantification of rigidity at rest.